Institutional settings and livelihood strategies in the Blue Nile Basin: implications for upstream/downstream linkages - Haileslassie, Amare; Hagos, Fitsum; Mapedza, Everisto D.; Sadoff, Claudia W.; Awulachew, Seleshi Bekele; Gebreselassie, S.; Peden, Donald G. (International Water Management Institute, 2008)
Through rapid assessment of existing literature and review of policy and other official documents, the report synthesizes the existing knowledge and gaps on policies and institutions and identifies key research issues that need in-depth study. The report provides an overview of the range of key livelihoods and production systems in the Blue Nile Basin (BNB) and highlights their relative dependence on, and vulnerability to, water resources and water-related ecosystem services. It also makes an inventory of current water and land related policies and institutions in the BNB, their organizational arrangements, dynamics and linkages and key policy premises. It highlights the major problems in institutional arrangements and policy gaps and makes suggestions for an in-depth Policy and Institutional Studies to be done as part of the Upstream-Downstream Research project.